Application of Electrocoagulation in Soy Milk Wastewater Treatment Process with Variation of Time and Voltage - Apriyanti, Mahyuni; Sutanto, Sutanto; Kusumawardani, Linda Jati (Helium: Journal of Science and Applied Chemistry, 2023)
Processing of soymilk liquid waste is carried out using the batch system electrocoagulation method. Variations in processing time are 20, 40, 60, 80, 100, and 120 minutes. The plate used is an aluminum plate measuring 10×5 cm. The electrode distance was 2 cm with an electrical voltage of 10 and 30 volts. The results of this research show that the best electrocoagulation process can reduce COD levels by 64.70%, TSS by 72.90% and increase the pH value to 5.17, however COD, TSS and pH levels are still above standard quality. Initial analysis results of soymilk wastewater with pH 4.06, COD 34408 mg/L, TSS 1550 mg/L, DO 0.30 mg/L, DHL 1090 μS/cm and Al 54.95 mg/L. After carrying out the electrocoagulation process, the pH value was 5.17, COD 12144 mg/L, TSS 420 mg/L, DO 0.37 mg/L, DHL 648 μS/cm and Al 231.33 mg/L at a voltage of 30 V with time. electrocoagulation 120 minutes.